2018
DOI: 10.1002/med.21552
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for the high‐affinity state of G‐protein‐coupled receptors with agonist tracers: Theoretical and practical considerations for positron emission tomography imaging

Abstract: The concept of the high‐affinity state postulates that a certain subset of G‐protein‐coupled receptors is primarily responsible for receptor signaling in the living brain. Assessing the abundance of this subset is thus potentially highly relevant for studies concerning the responses of neurotransmission to pharmacological or physiological stimuli and the dysregulation of neurotransmission in neurological or psychiatric disorders. The high‐affinity state is preferentially recognized by agonists in vitro. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 222 publications
(228 reference statements)
0
17
0
Order By: Relevance
“…Classical receptor binding assay studies have demonstrated that 5-HT 2A R (and other GPCRs) exist in two affinity states, a high- and a low- affinity state [ 23 , 24 , 25 ]. The affinity states of the receptors are considered to represent different functional states of the receptor, high-affinity being functionally active (activation of G αi1 -protein pathway) in contrast to the low-affinity state (activation of canonical G αq/11 -protein pathway) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classical receptor binding assay studies have demonstrated that 5-HT 2A R (and other GPCRs) exist in two affinity states, a high- and a low- affinity state [ 23 , 24 , 25 ]. The affinity states of the receptors are considered to represent different functional states of the receptor, high-affinity being functionally active (activation of G αi1 -protein pathway) in contrast to the low-affinity state (activation of canonical G αq/11 -protein pathway) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, however, [ 3 H] [Dmt 1 ]DALDA is not sensitive to sodium ions or Gpp(NH)p alone, and can bind to antagonist as well as agonist states of μ opioid receptors [31]. These are important considerations for potential imaging radioligands, since agonists typically bind only a small fraction of the receptor conformations available [54][55][56]. [Dmt 1 ]DALDA pharmacology is almost unique among μ opioid receptor agonists, but another prominent exception is [ 11 C]carfentanil, a full agonist of μ opioid receptors, which displays a low sodium effect that contributes to its suitability for brain imaging [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…While antagonists bind to receptors with a single affinity, agonists show two different affinities: high affinity for receptors coupled to G-proteins, and low affinity for uncoupled receptors (Figure 1). As reviewed recently (Shalgunov et al, 2019), these findings were demonstrated for various GPCRs: adrenergic (Hoffman and Lefkowitz, 1980), dopaminergic (Sibley et al, 1982; Leff et al, 1985), serotonergic (Battaglia et al, 1984; Gozlan et al, 1995; Watson et al, 2000) muscarinic (Ehlert, 1985), cannabinoid (Gullapalli et al, 2010), and opioid receptors (Law et al, 1985). The pharmacology of high-affinity receptors features specific phenomena: negative GTP cycle feedback loop, oligo-heterodimerization, internalization.…”
Section: Introductionmentioning
confidence: 87%